Integrating Islamic Narratives into Digital English Language Teaching - Weni Pratiwi; Ranidya Ayu Muthiah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
The incorporation of digital platforms in English as a Foreign Language (EFL) instruction offers significant potential for embedding culturally relevant content, especially in settings emphasizing moral education. This study is one of the first to investigate the use of Islamic narratives in digital EFL instruction in South Sumatra, focusing on how junior high school English teachers perceive and utilize these stories to enhance language learning and character development. Employing a qualitative case study methodology with eight teachers from public and Islamic schools, the findings indicate that teachers view Islamic narratives positively as tools for increasing student engagement and internalizing moral values. They effectively employ digital tools such as YouTube and WhatsApp to create culturally responsive instruction. However, challenges persist, including limited infrastructure and insufficient training. The implications of this research highlight the necessity of professional development programs and curriculum designs that integrate Islamic storytelling into EFL pedagogy. By contributing to the global discourse on culturally responsive pedagogy, this study emphasizes the importance of teacher digital literacy and localized content adaptation in diverse educational contexts.